Evaluation of CIP bred clones for expansion of potato production in the coastal areas of Bangladesh - Mahmud, A.A.; Hossain, M.; Kundu, B.C.; Rahaman, E.H.M.S.; Hasan, M.; Haque, E.; Rahman, A.; Alam Patwary, M.M.; Rahman, H.; Khan, S.I.; Kawochar, A.; Goswami, B.; et al. (Walter de Gruyter GmbH, 2016)
A set of International Potato Center (CIP)-bred potato clones was evaluated for their salt tolerance and productivity in replicated field trials in three coastal districts of Bangladesh, namely, Chittagong, Patuakhali and Satkhira. In each year of experimentation from 2011 to 2015, salinity levels increased progressively during the season and varied with time and place. Evaluation and selection were carried out using GGE biplot analysis and mean yield across the test sites; and the best performing clones were selected for the next year’s trial. Of the original fifteen test clones, two (CIP 301029.18 and CIP 396311.1) were selected for evaluation in the regional yield trial with cvs. Diamant and Asterix as checks. In the regional yield trial, across locations, CIP 301029.18 was the highest (21.8 ton/ha) and CIP 396311.1 (21.3 ton/ha) was the 2nd highest yielder such that CIP 301029.18 produced 64.0% higher yield and CIP 396311.1 produced 32.4% higher yield compare to their corresponding check varieties Diamant and Asterix. Similar ranking was found under farmers’ field conditions. Finally, these 2 clones CIP 301029.18 & CIP.